Gaya Arsitektur di Perumahan Dinas Militer Angkatan Darat, Cimahi, Jawa Barat - Milla Ardiani (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Cimahi is a city in West Java that owns many relics of the Dutch architectural heritage built in the early 20th century. The majority of buildings are military buildings that have a hierarchy according to the military rank, seen from the styles presented at the army's military housing. The building style has no longer presented either Indische empire style or modern colonial style. The architectural style in the transitional period at that time adapted the tropical climate of Indonesia with the visible formation of the Dutch. This paper is the result of research done by observation and a survey at the Army Military Housing, Cimahi, West Java. Data were analyzed quantitatively to analyze the number of houses and ornaments dismantled and its original form. In addition, qualitative methods are also used to analyze the demolitions done by the building occupants.